2020
DOI: 10.5735/086.057.0105
|View full text |Cite
|
Sign up to set email alerts
|

Social Wasps (Vespinae) in Urban Gardens and Woods

Abstract: Global change, including urbanization, affects species ecology. Social wasps (Vespinae) are ubiquitous in urban areas, which increases their encounters with humans. We studied social wasps in urban gardens and nearby urban woods in central Finland, using beer traps. Social wasps were common in gardens and woods, and overall wasp abundance was higher in the woods. Also, the most abundant and frequent species Vespula vulgaris was more abundant in the woods than in the gardens. Variation in the overall abundance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Additionally, they become much more of a human nuisance because they contain orders of magnitude more workers than a typical nest (Beggs et al, 2011 ; Lester & Beggs, 2019 ; Wilson & Holway, 2010 ; Wilson et al, 2009 ). Vespula perennial colonies are expected to increase their range in response to climate change, which will further increase negative interactions with humans (Demain, 2020 ; Komonen et al, 2020 ; Lester et al, 2017 ). Moreover, it has been found that relatively few Vespula wasps are needed to initiate a new introduced population (Brenton‐Rule et al, 2018 ; Chau et al, 2015 ; Dobelmann et al, 2019 ; Eloff et al, 2020 ; Hanna et al, 2014 ; Schmack et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they become much more of a human nuisance because they contain orders of magnitude more workers than a typical nest (Beggs et al, 2011 ; Lester & Beggs, 2019 ; Wilson & Holway, 2010 ; Wilson et al, 2009 ). Vespula perennial colonies are expected to increase their range in response to climate change, which will further increase negative interactions with humans (Demain, 2020 ; Komonen et al, 2020 ; Lester et al, 2017 ). Moreover, it has been found that relatively few Vespula wasps are needed to initiate a new introduced population (Brenton‐Rule et al, 2018 ; Chau et al, 2015 ; Dobelmann et al, 2019 ; Eloff et al, 2020 ; Hanna et al, 2014 ; Schmack et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Global environmental changes, including climate change, affect the behavior, range, and abundance of wasps. For instance, the German wasp, Vespula germanica, native to central and southern Europe, has expanded its range north to Finland (Sorvari 2018;Komonen et al 2020). In Finland, several exceptionally hot and long summers in the 2010s facilitated wasp communities to grow large.…”
Section: Environmental Changes and Increasing Human-wasp Encountersmentioning
confidence: 99%
“…While we aimed for a genuinely interdisciplinary research narrative, the different sub-studies and datasets are in different roles in the paper. Results from the ecological research have already been published in Komonen et al (2020), Komonen and Torniainen (2022), and Torniainen and Komonen (2021), and here they are referred to as secondary material. We also refer anecdotally to unpublished work, including questionnaires for high-school and university students, material obtained from a citizen science survey, and observations from collaboration with a pest management company 1 .…”
Section: An Interdisciplinary Multispecies Studymentioning
confidence: 99%
See 2 more Smart Citations